Comparison of External Carotid Ligation and Preope Embolization of Feeding Vessel for Controlling Perop Heamorhage in Angiofibroma Excision - Bakht Aziz, Zahra Aleem, M. Atiq U Rehman, M. Umair Wahab, Irshad Malik, Kashif Iqbal Malik, Hasnain Haider, Maryam Umar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The prevalence of Angiofibroma of juvenile variety is infrequent tumor of nasopharynx7. It grows aggressively and is locally destructive and extends into the cranium as well. Its symptoms usually involve nasal obstruction with or without nasal bleed. Aims: To compare two methods i.e 1. Carotid artery ligation per operatively and embolization of feeding artery pre operatively in order to assess which method is better in controlling per operative bleeding during its excision. Design: Comparative study Study setting: The study was conducted in the Department of Otorhinolaryngology of Jinnah Hospital, Lahore. The duration of the study is from 01st January 2020 to 31st January 2022. Methodology: A group 20 patients were taken having angiofibroma. 10 patients went for pre operative embolization of the feeding vessel of the angiofibroma after localizing the vessel by having MRA. The other 10 patients had their external carotid artery ligated before excising the angiofibroma. The bleeding which occurred during both procedures was quantified by weighing the gauze pieces soaked per operatively, the blood collected in suction bottle and then comparing the values. Results: Ten patients who had embolization had far more bleeding during excision as compared to the 10 patients who had their external carotid artery ligated per operatively before excision. Conclusion: Results showed that pre operative embolization is not a better procedure to control per op bleeding as compared to external carotid artery ligation during angiofibroma excision.